Transaction Analyzer Using Graph-Oriented Data Structures - Banerjee, Abhishek; Goldstein, Daniel G.; Arnetoli, Roberto; Darbare, Pravin; Lai, Kevin; Saraf, Sanjay (2018)
Techniques described herein relate to generating graph-oriented data structures based on cross-channel multi-user transaction and/or interaction data from one or more data sources, Additional techniques relate to analyzing and processing transactions using the graph-oriented data structures. Transaction data may be received from various data sources, and analyzed to determine subsets of the transaction data relating to interactions between specific pairs of users. Graph-oriented data structures may be generated based on the subsets of transaction data relating to the specific pairs of users, and may be used to analyze and process transaction requests.
US Patent Application